On-line Condition Monitoring and Evaluation of Remaining Useful Lifetimes for Mineral Hydraulic and Turbine Oils - Tič, Vito; Lovrec, Darko (University of Maribor Press, 2017)
Condition monitoring of hydraulic and turbine oils, and especially their remaining useful life, become a more important strategic business advantage for a plant owner, environment protection and cost reduction. This monograph discusses this problem: Condition monitoring of hydraulic fluids throughout their life-cycles. Particular emphasis is placed on assessing mineral-based oils’ conditions and their remaining useful lifetimes quantitatively. Practicality and usefulness are vital when developing and deploying various methods for condition monitoring systems within industrial environments. Therefore, it is important to know the oil degradation mechanisms and influencing factors, commonly used laboratory methods and oil ageing tests, and. for on-line condition monitoring system design, the available sensors with all their characteristics and restrictions. The proposed approach is based on a novel method for testing the durability and oxidation stabilities of different hydraulic and turbine oils. The developed mathematical model is based on data from previously conducted oil-ageing tests for the assessment of an oil’s condition and its remaining useful lifetime. The method can also be used for comparison of different oils, and for selecting a more adequate oil with high oxidation stability and long service-lifetime.